Macro-scale (biomes) differences in neotropical stream processes and community structure - Feio, Maria João; Leite, Gustavo Figueiredo Marques; Rezende, Renan S.; Medeiros, Adriana Oliveira; Cruz, Lorena C.; Dahora, Juliana AS; Calor, Adolfo Ricardo; Neres-Lima, Vinicius; Silva-Araújo, Monalisa; Callisto, Marcos; França, Juliana Silva; Martins, Isabela; et al. (Global Ecology and Conservation, 2018)
The definition of conservation strategies and ecological assessment schemes requires understanding ecosystem patterns over multiple spatial scales. This study aimed to determine if macro-scale structural and functional (processes) patterns associated with stream ecosystems differed among three neotropical biomes (Cerrado, Amazon, Atlantic Forest). We compared the aquatic communities (benthic invertebrates and hyphomycetes) and processes (decomposition rates, primary production and biofilms growth and aquatic hyphomycetes reproduction rates-sporulation) of Cerrado stream sites (neotropical savannah) against those of stream sites in the connecting biomes of the Atlantic Forest and Amazon (rainforests). We expected that, contrary to the biome dependency hypothesis the community structure and processes rates of streams at the biome-scale would not differ significantly, because those ecosystems are strongly influenced by their dense riparian forests, which have a transitional character among the three biomes. Fifty-three stream sites were selected covering a wide range of geographic locations (Table 1), from near the Equator (2° S) in the Amazon, to intermediate latitudes in the Cerrado (12-19° S), and latitudes closer to the tropic of Capricorn in the Atlantic Forest (19º-25° S). We found that: 1) at the abiotic level, the aquatic ecosystems of the three biomes differed, which was mostly explained by large-scale factors such as temperature, precipitation and altitude; 2) functional and structural variables did not behave similarly among biomes: decomposition and sporulation rates showed larger differences among biomes than invertebrate and aquatic hyphomycete assemblages structure; 3) invertebrate assemblages structure differed between the rainforests and Cerrado but not between rainforests (Amazon and Atlantic Forest) whereas aquatic hyphomycetes were similar among all biomes; 4) biofilm growth and algae concentration in biofilms of artificial substrates were highly variable within biomes and not significantly different between biomes. Overall, aquatic ecosystem processes and community structure differed across biomes, being influenced by climatic variables, but the variation is not as pronounced as that described for terrestrial systems. Considering the potential use of these functional and structural indicators in national-wide ecological assessments, our results indicate the need to define different reference values for different biomes, depending on the variable used. The approach followed in this study allowed an integrative analysis and comparison of the stream ecosystems across three tropical biomes, being the first study of this kind. Future studies should try to confirm the patterns evidenced here with more sites from other areas of the three biomes, and especially from the Amazon, which was the least represented biome in our investigation. © 2018